PENERAPAN KOMPRES HANGAT TERHADAP INTENSITAS NYERI PERSALINAN - Stefani Anastasia Sitepu (Jurnal Pengabdian Masyarakat Putri Hijau, 2022)
Childbirth is a process of giving birth that occurs naturally with uterine contractions in the mother which is passed by opening to expel the baby. The scientific procedure is where cervical dilatation occurs, the birth of the baby and the placenta from the mother's womb (Beautiful, Firdayanti, 2019). Pain is an unpleasant emotional and sensory experience due to actual and potential tissue damage (Surbakti, 2017). One of the non-pharmacological methods of reducing labor pain is the application of warm compresses. A warm compress is giving a warm feeling to the patient to fulfill a need for comfort. Warm compresses are a procedure for using local temperatures which can cause some physiological effects (Agustiningrum, 2015). The first activity carried out was by inviting 18 pregnant women to attend the pregnancy exercise and distributing leaflets about education on warm compresses in reducing the intensity of labor pain. Before the warm compress is carried out, pregnant women will first take part in a pre-test to measure the initial knowledge of pregnant women regarding the application of warm compresses in reducing pain intensity during labor. After that, warm compresses are carried out. At the end of the session, pregnant women were asked to fill out a post-test and provide an evaluation regarding the activities that had been carried out. Pregnant women will be observed after doing warm compresses by evaluating how often pregnant women do warm compresses. Pregnant women who apply warm compresses experience a reduction in pain during the third trimester of pregnancy by 55.5%.